(untitled) (Biological Sciences - PJSIR, 2001)
Anexperiment wasconducted toseetheeffectofhigherlevelsof rapeseedcake(15,20 and25%) inpoultrydiet onthe performance of laying hen (Tetra SL). All the diets were isocaloric (within the range of 319 to 321 kcal 100 g:’), isoproteinacious (17.19 to 17.31%) and the fibrecontents were within the recommended range (2.98 to 3.52%). The experiment wasof28 daysduration. Eggsizewasmaximumforthe20%repeseedcakegroup (62.25g)followed bythe 25% group (61.24 g) and minimum for 15%rapeseed cake group (58.26 g). Egg size of standard group was 58.99 g. The egg laying percentage was 60% for standard group and 59.33% for 25% rapeseed group. No difference in birds live weight was observed due to feed variationthroughout theexperimental period.No mortality was recorded. Orga- noleptic evaluation by trainedjudges revealed no difference in overall acceptability of eggs by all the groups.